Análisis y diseño de una arquitectura inalámbrica de acceso seguro basada en autoridad de certificación - Mendoza Garay, Omar Stalin (2012)
The objective of this thesis is the analysis and design of a secure wireless architecture based certification authority, for it has made a study of the authentication mechanisms and the creation of a Public Key Infrastructure (based on OpenSSL), which will allow us to create the certification authority and thus be able to create and sign digital certificates, all in conjunction with the RADIUS protocol and RADIUS authentication server (based on FreeRADIUS), will enable user authentication using sessions TLS. This will greatly improve the security of access and data transmission in wireless networks